1998
DOI: 10.1152/jappl.1998.84.2.576
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender dependency of baroreflex sensitivity in healthy subjects

Abstract: We evaluated the correlates of baroreflex sensitivity (BRS) in healthy subjects. The study consisted of 117 healthy, normal-weight, nonsmoking male and female subjects aged 23-77 yr. Baroreflex control of heart rate was measured by using the phenylephrine bolus-injection technique. Frequency- and time-domain analysis of heart rate variability and an exercise test were performed. Plasma norepinephrine, epinephrine, insulin, and arginine vasopressin concentrations and plasma renin activity were measured. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
216
11
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(265 citation statements)
references
References 32 publications
29
216
11
9
Order By: Relevance
“…10 Indeed, the gender-related difference in BRB in the present study was almost as great as the difference recently found between healthy adults and patients with long-standing essential hypertension. 10,16 Thus, consistent with previous reports of gender-related differences in other ANS-cardiovascular functions, [1][2][3][4]8,[23][24][25] the present findings indicate that subject gender is a major source of interindividual variability in tonic ANS support of BP and BRB of BP in healthy adult humans.…”
Section: Discussionsupporting
confidence: 91%
“…10 Indeed, the gender-related difference in BRB in the present study was almost as great as the difference recently found between healthy adults and patients with long-standing essential hypertension. 10,16 Thus, consistent with previous reports of gender-related differences in other ANS-cardiovascular functions, [1][2][3][4]8,[23][24][25] the present findings indicate that subject gender is a major source of interindividual variability in tonic ANS support of BP and BRB of BP in healthy adult humans.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous findings in patients with chronic MI 17 and in healthy subjects, 18 we found only weak correlations of norepinephrine concentrations with baroreflex response. In the present study, norepinephrine concentrations were significantly higher in patients with incomplete reperfusion, reflecting a higher background efferent sympathetic activation.…”
Section: Norepinephrine Concentrations and Baroreflex In Acute MIsupporting
confidence: 93%
“…The majority of studies have shown that BRS is reduced during HUT [41][42][43], while a few studies have reported that it is augmented [30]. Thus, BRS changes in this study were virtually consistent with the former results.…”
Section: Brs Responsesupporting
confidence: 89%
“…Given that BRS decreases as age increases [43], and thus is a confounding factor, we examined the correlation of age with BRS using regression analysis. We found no significant correlation in either group between age and BRS.…”
Section: Confounding Factorsmentioning
confidence: 99%